The Effect of Microsurgery Inguinal Varicocelectomy by Secondary Infertile Male Patients with Clinical Varicocele - Badur, Namık; Karakeçi, Ahmet (Fırat University, 2014)
Objective: To investigate effect of Microsurgery Inguinal Varicocelectomy by treating varicocele in secondary infertile patients. Material and Method: Sixty primary infertile and thirty secondary infertile patients whom were referred to andrology clinic due to infertility and undergone Microsurgery Inguinal Varicocelectomy operation because of varicocele presence, were retrospectively investigated. Patients were asses-sed according to age, duration of the infertility history, grade of varicocele, pre and postoperative semen parameters and pregnancy rates. Results: No any significant difference were determined in the pre and postoperative semen parameters in two groups (p>0,05). It was detected that sperm motility and number of total motile sperms with primary infertile group and number of spermia, motile spermia and sperm motility by secon-dary infertile group have statistically significantly increased after surgical procedure (p

Amaç: Varikosel tedavisinde uygulanan Mikrocerrahi İnguinal Varikoselektomi'nin sekonder infertil hastalardaki etkinliğini araştırmak. Gereç ve Yöntem: Androloji polikliniğine infertilite nedeni ile başvuran ve klinik varikosel tanısıyla Mikrocerrahi İnguinal Varikoselektomi operas-yonu yapılan 60 primer infertil ve 30 sekonder infertil hasta retrospektif olarak incelendi. Hastaların yaşları, infertilite süreleri, varikosel dereceleri (grade), operasyon öncesi ve operasyon sonrası semen parametreleri ve gebelik oranları değerlendirildi. Bulgular: Operasyon öncesinde ve operasyon sonrasında semen parametreleri açısından her iki grup arasında anlamlı fark olmadığı saptandı (p>0,05). Primer infertilite grubunda operasyon sonrası, operasyon öncesine göre sperm motilitesinin ve total motil sperm sayısının, sekonder infertil grupta ise sperm sayısının, sperm motilitesinin ve total motil sperm sayısının anlamlı olarak daha yüksek olduğu tespit edildi (p
Klinik Varikoseli Olan Sekonder İnfertil Erkek Hastalarda Mikrocerrahi İnguinal Varikoselektominin Etkinliği